Influence of the polyvinyl pyrrolidone concentration on particle size and dispersion of ZnS nanoparticles synthesized by microwave irradiation - Soltani, Nayereh; Saion, Elias; Haghiri, Maryam Erfani; Saraee, Khadijeh Rezaee Ebrahim; Bahmanrokh, Ghazaleh; Drummen, Gregor P. C.; Bahrami, Afarin; Hussein, Mohd Zobir (MDPI AG, 2012)
Zinc sulfide semiconductor nanoparticles were synthesized in an aqueous solution of polyvinyl pyrrolidone via a simple microwave irradiation method. The effect of the polymer concentration and the type of sulfur source on the particle size and dispersion of the final ZnS nanoparticle product was carefully examined. Microwave heating generally occurs by two main mechanisms: dipolar polarization of water and ionic conduction of precursors. The introduction of the polymer affects the heating rate by restriction of the rotational motion of dipole molecules and immobilization of ions. Consequently, our results show that the presence of the polymer strongly affects the nucleation and growth rates of the ZnS nanoparticles and therefore determines the average particle size and the dispersion. Moreover, we found that PVP adsorbed on the surface of the ZnS nanoparticles by interaction of the C-N and C=O with the nanoparticle's surface, thereby affording protection from agglomeration by steric hindrance. Generally, with increasing PVP concentration, mono-dispersed colloidal solutions were obtained and at the optimal PVP concentration (5%), sufficiently small size and narrow size distributions were obtained from both sodium sulfide and thioacetamide sulfur sources. Finally, the sulfur source directly influences the reaction mechanism and the final particle morphology, as well as the average size.